An urban partisan: Carl Schmitt’s and Jacob Taubes’ guide for urban revolution - Nawratek, Krzysztof (Journal of Architecture and Urbanism, 2014)
The contemporary neoliberal city exists within the context of the immateriality of the contemporary economy, the dominance of financial speculation over commodity exchange and the transition of the city from the political subject to a mere resource used by global corporations and institutions (Hirst 2005; Harvey 2012; Marazzi 2010). There is an obvious conflict between the city as a material entity, and the immaterial forces of global capitalism. In this context, Carl Schmitt and Jacob Taubes provide useful tools with which to create a theoretical framework to re-establish discussion of the city as a political and economic subject. I will begin by referring to Schmitt’s considerations of territory and the conflict between the telluric logic, the sea logic and the air logic as presented in his work ‘The Nomos of the Earth in the International Law of the Jus Publicum Europaeum’ (Schmitt 2003). I will continue by discussing Jacob Taubes, who in his Occidental Eschatology (Taubes 2009) provided the tools with which to reject the Heideggerean, reactionary understanding of place, and invented a new type of place – the ‘Taubesian place’, a place where a revolution could be started. As a theoretical context for these considerations, I have referenced the Partisan figure presented by Schmitt (2004), through Taubes considerations of space and history.